Poster: Sensor localization system for AR-assisted disaster relief applications - Choi, Hong Beom; Lim, Keun Woo; Ko, Young Bae (MobiSys 2019 - Proceedings of the 17th Annual International Conference on Mobile Systems, Applications, and Services, 2019)
In this poster, we propose a sensor localization system assisted by wireless communication and augmented reality (AR) suitable for disaster relief applications. Generally, disaster environments are considered extremely hazardous and deteriorated, with unpredictable effects to human mobility and digital devices. To maximize the safety and efficiency of first responders, deployment of wireless sensors are of utmost importance, as sensor nodes can provide sensing information as well as location information. We analyze the issues and challenges that need to be tackled for high accuracy localization of sensor nodes in such environments, and then propose a system that we plan to develop in the near future.
Keywords: Disaster relief; Issues and challenges; Localization of sensor nodes; Location information; Safety and efficiencies; Sensor localization; Visual odometry; Wireless communications; Disaster relief; Sensor localization; Visual odometry